A procedure for validating rigid catenary models using evolutionary techniques - Simarro-Vega, Montserrat; Postigo-Pozo, Sergio; Cabrera-Carrillo, Juan Antonio; Castillo-Aguilar, Juan Jesús (Elsevier, 2020)
This paper describes a method to validate rigid catenary finite element models from modal tests. The model parameters are obtained by means of an optimization process using evolutionary techniques. The validation of rigid catenary sections is a complicated process due to the large number of parameters to be tuned. Three different scenarios have been studied to reproduce the most common assemblies of real rigid catenary sections. The performance of the algorithm has been evaluated using 45 virtual models of rigid catenary assemblies with section lengths from 48 up to 480 m and span lengths ranging from 8 to 12 m. The influence of errors in the installation of the supports has also been studied. In all cases, the algorithm has demonstrated its effectiveness in providing the correct model parameters even when a sin- gularity in some of its supports has been introduced. According to the results, the proposed method is a valid tool to validate rigid catenary mathematical models.
Keywords: Curvas - Análisis matemáticos; Overhead conductor rail; Finite element; Experimental modal analysis; Evolutionary algorithms; Rigid catenary; Genetic algorithm